INTRODUCTION OF OCCUPATIONAL SAFETY AND HEALTH (K3) PRINCIPLES IN BLACKSMITHS VILLAGE - Achmad Djalaluddin, Nurgadima; Maharja, Rizky; Mifta Farid Panggeleng, Andi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Background: One of the more ancient occupations is blacksmithing, which involves risky and dangerous work in the unorganized sector. Blacksmithing's risks and hazards must be understood and managed in order to prevent workplace accidents and illnesses. Objective: Blacksmiths are to be introduced to occupational safety and health concepts through this exercise. Methods: Blacksmiths from Pamboborang Village in Majene Regency participated in this endeavor as partners. utilizing Personal Protective Equipment (PPE), which is broken down into three stages of activity—preparation, implementation, and evaluation—the stages of carrying out the activities are carried out in an approach through discussion, education/counseling, and practice utilizing PPE. There were 27 blacksmiths who took part in this activity. Result: Participants are given information on workplace hazards and risks and control measures that can be implemented. Participants were also given basic K3 information. Participants were also taught about the many types and benefits of personal protective equipment (PPE) and practiced using it. Conclusion: Community service activities in the form of an introduction to K3 principles in the blacksmith community are progressing well and according to the plan.